Communicative Situation of Oral Professional Communication within English-Language Medical Discourse - M. S. Nevzorova (Научный диалог)
The article is devoted to scientific and professional communication between specialists in one of the fields, namely the medical discourse. The research is based on English texts of the dialogues of the doctors from the TV series “House” and “ER” as well as the texts of scientific and medical discussions, freely available on the Internet. The objective characteristics of the communicative situation are identified and described. It is proved that the dominants of communicative situation of scientific and professional communication are institutional character, formality / informality of the situation, communicative goal, language of scientific and professional communication, communication modus. Special attention is given to professional language subsystem. The typology of physician’s professional language is proposed with the identification of groups of vocabulary related to medical terminology and medical jargon. The latter group includes medical slang and professionalisms. Variation is observed in switching terminology busy code to the code based on the medical parlance. The novelty of the research lies in the fact that medical professional communication qualifies as equal status communication because it is a collaboration of specialists. The author divides the situation of symmetric and asymmetric communication modes. The features of such communicative events as discussion of private clinical case and medical research discussion are commented. Each of them has a list of signs that determine the peculiarities of communicative behaviour of the participants of the situation.